Pengaruh Program Acara Talk Show Bugar Bersama Ade Rai Terhadap Pemenuhan Kebutuhan Informasi Pendengar Tentang Kebugaran di Radio PR 107.5 FM Kota Bandung - Tatan Gunawan (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This research focuses on how far the influence of the talk show Bugar Bersama Ade Rai contained in Radio PRFM Bandung in meeting the information needs of listeners about fitness. The research method used is explanatory survey method with quantitative approach and sampling technique used is accpore porpusive sampling. The population of the research were the listeners of the talk show Bugar Bersama Ade Rai in Radio PRFM Bandung and sample of the research were the listeners who often contact the announcer in the question and answer session. Technical analysis of data used is the technique of path analysis and inferential analysis used is the correlation coefficient by using Pearson correlation formula. The results showed the intensity of Talk Show Bugar with Ade Rai influenced both directly to meet the information needs of radio listeners, even indirectly through the content materials and actualization. The content of Talk Show Bugar together with Ade Rai has an effect both directly on the fulfillment of information needs of radio listeners, even indirectly through the intensity and actualization. Whereas the motive of the actualization of Talk Show listeners with Ade Rai has a good effect directly on the fulfillment of information needs radio listeners, even indirectly through the intensity and content of the material. The intensity, content and motive of the actualization of the listeners Talk Show Fit together with Ade Rai influence together towards the fulfillment of information needs of radio listeners